2017
DOI: 10.3945/ajcn.117.153072
|View full text |Cite
|
Sign up to set email alerts
|

Dietary long-chain fatty acids and carbohydrate biomarker evaluation in a controlled feeding study in participants from the Women’s Health Initiative cohort ,

Abstract: Biomarkers of macronutrient intake are lacking. Controlled human feeding studies that preserve the normal variation in nutrient and food consumption are necessary for the development and validation of robust nutritional biomarkers. We aimed to assess the utility of serum phospholipid fatty acids (PLFAs) as biomarkers of dietary intakes of fatty acids, total fat, and carbohydrate. We used an individualized controlled feeding study in which 153 postmenopausal women from the Women's Health Initiative (WHI) were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
0
26
0
2
Order By: Relevance
“…Association between PA levels in blood fraction in relation to breast cancer risk has been reported in a meta-analysis (Saadatian-Elahi et al, 2004 ) and a prospective study (Bassett et al, 2016 ), whereas another prospective study conducted in northern Italy found no association between saturated fatty acids and breast cancer risk (Pala et al, 2001 ). Since changes in PA intake do not influence significantly its tissue concentration (Innis and Dyer, 1997 ; Song et al, 2017 ), it implies that DNL has a central role in cancerogenesis.…”
Section: Dnl and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Association between PA levels in blood fraction in relation to breast cancer risk has been reported in a meta-analysis (Saadatian-Elahi et al, 2004 ) and a prospective study (Bassett et al, 2016 ), whereas another prospective study conducted in northern Italy found no association between saturated fatty acids and breast cancer risk (Pala et al, 2001 ). Since changes in PA intake do not influence significantly its tissue concentration (Innis and Dyer, 1997 ; Song et al, 2017 ), it implies that DNL has a central role in cancerogenesis.…”
Section: Dnl and Cancermentioning
confidence: 99%
“…The liver plays a central role in regulating body concentration of PA, through its desaturation to POA or elongation to SA and further desaturated to OA. As a matter of fact, its plasma concentrations, in physiological conditions, are not significantly influenced by PA dietary intake (Innis and Dyer, 1997 ; Song et al, 2017 ), suggesting that the homeostatic control of PA concentration in the liver is regulated by its production via DNL on one side and its desaturation on the other.…”
Section: Pa Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Other modifiable factors that may influence DNL include sleeping behavior and meal frequency [39]. Dietary intakes of saturated and monounsaturated fatty acids directly influence 16:0, 16:1n7, 18:0, and 18:1n9 [38,40,41], but it remains unclear whether these effects are similar or even smaller than the influence of endogenous synthesis and metabolism in long-term settings [42][43][44]. For example, limited evidence from Swedish cohorts suggests the negative or null association of carbohydrate intake with concentrations of DNL-related fatty acids in adipose tissue and phospholipids and highlight a role of saturated fat or alcohol as determining DNL fatty acids [45,46].…”
Section: Plos Medicinementioning
confidence: 99%
“…Prominent examples of nutritional biomarkers include a doubly-labeled water (DLW) biomarker of energy intake (Schoeller, 1999), a urinary nitrogen biomarker of protein intake (Bingham, 2003), and 24-hour urine-based measures of sodium and potassium intake (Luft, Fineberg, & Sloan, 1982; Rakova et al, 2013). Additionally, our research group, using data from a 153-woman human feeding study, has recently proposed novel biomarkers for the intake of several carotenoids and tocopherols using blood serum concentrations measurements (Lampe et al, 2017), and a carbohydrate biomarker using plasma fatty acid profiles (Song et al, 2017). These latter biomarkers required the inclusion of certain study subject variables for (1) to be plausible.…”
Section: Nutritional Biomarker Development Methodsmentioning
confidence: 99%